Theoretical description for sucralose cathodical electrochemical determination on the conducting polymer, containing pyridinic nitrogen atoms - Tkach, V. V.; Storoshchuk, N. M.; Storoshchuk, B. D.; Kopiika, V. V.; Luganska, O. V.; Omelyanchik, L. O.; Gencheva, V. I.; Yeshchenko, Y. V.; Kormosh, Z. O.; Nazymok, Y. V.; Moysiuk, V. D.; Rusnak, V. F.; et al. (My University, 2022)
A novel process for sucralose cathodically electrochemical determination has been suggested. In this process, the conducting polymer with pyridinic nitrogen atoms reacts specifically with sucralose, yielding a salt. This salt is thereby reduced gradually, yielding a less conducting macromolecule. The analysis of the correspondent mathematical model, realized through the linear stability theory and bifurcation analysis, shows that the oscillatory behavior is more probable to be realized due to charge changes and rearrangements during the electroanalytical process its influence on the surface and DEL conductivity. Nevertheless, this process may be efficient for the sucralose electrochemical determination.
Keywords: sucralose; electrochemical sensor; conducting polymer; electrochemical oscillations; stable steady-state